STATE ACTORS AND VIOLENCE AGAINST CHILDREN IN NIGERIA: A CRIMINOLOGICAL PERSPECTIVE - Ahingir, Terfa Mathew; Eraye, Michael Christopher; Haazande, Terver; Dauda, Likita (African Journal of Social and Behavioural Sciences, 2024)
Nigeria’s young population is one of its greatest assets, yet the country’s children continue to face significant threats to their well-being and safety. Despite the ratification of international treaties and laws to protect children, violence against children remains a pressing issue in Nigeria, with state actors often playing a role in perpetuating and condoning this violence. This paper examines violence against children by state actors in Nigeria. The study objectives were to investigate the forms of violence perpetrated against children by state actors; and how security agencies and the justice system perpetrated violence against children in Nigeria. Routine activity theory was used to explain state actors` activities in Nigeria. This study utilized secondary data. Data was analysed qualitatively. The study found that children are exposed to various kinds of violence, including physical, psychological, emotional and sexual violence. Additionally, systemic issues within the judicial system have resulted in unintended consequences that contribute to the perpetuation of VAC, such as delays in court processes, inadequacies in child protection measures, cultural norms, and a lack of resources. The study recommended effective implementation of children’s rights in Nigeria, particularly for the most vulnerable and marginalized children. Additionally, public awareness campaigns should be launched to educate citizens on children’s rights and how to report abuses.